(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water is an essential for life, economic activities, and agricultural productivity, making effective water management essential in regions like Tirunelveli District. This study explores water consumption across domestic, agricultural, and industrial sectors, assesses current water supply schemes, and evaluates methods for improving water conservation and demand management. By analyzing water usage patterns, the study highlights agriculture’s significant role in water consumption and the widespread use of efficient irrigation systems. Findings suggest that strategies like rainwater harvesting, industrial water recycling, and public awareness campaigns are crucial for ensuring the district’s sustainable water future.